Kadar Kortisol Saliva Sebagai Penanda Gangguan Gejala Menopause pada Paramedis Poli Rawat Jalan Usia Perimenopause di Rumah Sakit Umum Pusat Haji Adam Malik Medan - Yufi Permana; M. Fidel Ganis Siregar; Syamsul A. Nasution; Sanusi Piliang; Muldjadi Affendy; Yostoto B. Kaban (Fakultas Kedokteran USU, 2015)
Introduction :The premenopausal period is characterized as a decline in estrogen levels that consequently result in disturbing symptoms. One noted significant factor in this period is the psychological state, a condition that is closely related to cortisol levels. Stress is known to be a product of the neuroendocrine system. As a product of tbis mechanism, cortisol is frequently used as a biomarker to study stress. Currently, menopausal symptoms are diagnosed based on present complaints, which tends to be subjective, consequently, a biomarker is required to diagnose menopausal disturbances. Method :This analytic, diagnostic, cross sectional study was conducted in the General Hiospital of Haji Adam Malik Medan, and enrolled paramedics working at the out patient clinic from March until April 2015. All subjects were asked to fill a Menopause Rating Scale (MRS), the results of which were then associated with obtained salivary cortisol levels. Results :Salivary cortisol levels was significantly associated with menopausal disturbances with p< 0.01. Salivary cortisol also significantly differed based on each MRS scores with p=0.008. A cut-off value of 9.52 ng/ml was obtained, with specificity and sensitivity values of 85 and 77%, respectively. Conclusion :Salivary cortisol testing as a marker for menopausal disturbances obtained a marker of 9.52 ng/mL with specificity and sensitivity values of 85 and 77%, respectively. Key words :Salivary cortisol, menopausal disturbances, Menopause Rating Scale